Damping Identification with Acceleration Measurements Based on Sensitivity Enhancement Method - Xusheng Wang; Kun Liu; Hongbo Liu; Yuhan He (Shock and Vibration)
The damping is important for forward and inverse structural dynamic analysis, and damping identification has become a hot issue in structural health monitoring recently. The dynamic responses of the structure can be measured in practice, and the structural parameter usually can be identified by inverse response sensitivity analysis. To reduce the measurement noise effect and enhance the effectiveness of the response sensitivity method, an enhanced sensitivity analysis method was proposed to identify the structural damping based on the Principal Component Analysis (PCA) method. The measured acceleration responses were analyzed by PCA method, and the updated analytical responses and the response sensitivities were projected into the subspace determined by the first-order principal component. The projection equations were adopted to identify the parameters of damping model. The proposed damping identification method was numerically validated with a planar truss structure at first, and then the experimental study was conducted with a steel planar frame structure. It shows that the proposed method is effective in identifying the parameters of damping model with better accuracy compared with the conventional acceleration response sensitivity method, and it is also robust to the sensor placement and measurement noise.